2012
DOI: 10.1007/s12199-011-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect significant association between estrogen receptor-alpha gene polymorphisms and endometriosis in Japanese women

Abstract: Objectives The aim of the study was to test whether estrogen receptor 1 (ESR1) gene polymorphisms are correlated with the risk of the development of endometriosis in Japanese women, as a preliminary study. Methods To compare allelic frequencies and genotype distributions, a case-control study of 100 affected women and 143 women with no evidence of disease was performed using 10 microsatellite repeat markers and 66 single-nucleotide polymorphisms (SNPs) in the ESR1 gene region. Results Although our results migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Some studies indicate that common genetic variants within ER cofactor genes are unlikely to play significant role in endometrial cancer risk in the European population [91]. In a further study the c.454-397C→T CC and c.454-351A→G GG genotypes were associated with a decreased risk for endometrial cancers [92].…”
Section: Presumed Role Of Gene Polymorphism In the Alterations Of Estmentioning
confidence: 80%
“…Some studies indicate that common genetic variants within ER cofactor genes are unlikely to play significant role in endometrial cancer risk in the European population [91]. In a further study the c.454-397C→T CC and c.454-351A→G GG genotypes were associated with a decreased risk for endometrial cancers [92].…”
Section: Presumed Role Of Gene Polymorphism In the Alterations Of Estmentioning
confidence: 80%
“…In a case-control study, patients homozygous for the ESR1 C allele polymorphism rs2234693 were found to be associated with a significantly augmented risk of leiomyoma (61). However, in a case-control study of 100 cases, ESR1 polymorphisms did not seem to contribute to disease susceptibility (152). In a similar study, infertile women with the ESR1 rs9340799 GG genotype presented a 4-fold higher risk of endometriosis (153).…”
Section: Genetic Association Studiesmentioning
confidence: 96%
“…Previous reports have shown associations of ESR1 genetic variants with susceptibility to endometriosis and fertility status [6, 813], but many studies failed to achieve an association regarding ESR1 variants and endometriosis-related infertility [9, 1416]. Interestingly, Lamp et al linked ESR1 SNPs only to endometriosis without infertility [12], while Wang et al associated ESR1 rs3798573 with risk of both endometriosis and infertile endometriosis in Han Chinese women [13].…”
Section: Introductionmentioning
confidence: 99%